Analysis of Students’ Statistical Literacy on Self Organized Learning Environment (SOLE) Learning Model - Nuzul Putri Rahmawati; Moh. Asikin; Mariani Scolastika (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
The purpose of study to described student’s literacy analysis using Self-Organized Learning Environment (SOLE) learning model. The low student’s statistical literacy ability as one of the abilities needed facing problems in today’s society. Therefore, the problem became background of this study. By utilizing Internet accessibility and the environment in the Self-Organized Learning Environment (SOLE) learning model, it was possible for authentic learning and twenty-first century development skills to mature. This study used to Self-Organized Learning Environment (SOLE) learning model, which students self-organized in groups and learned to use computers connected to the internet with minimal teacher support. This study also used mix methods. Students' statistical literacy ability using the Self-Organized Learning Environment (SOLE) learning model was analyzed by descriptively. The result of study was a statistical analysis of the literacy of 32 students with the following details: 28.125% of students had statistical literacy in the high category, 40.625% students had statistical literacy in the medium category, the remaining 31.25% students were in the low category.